Analisa Pengaruh Posisi Biji pada Malai Terhadap Gaya Perontokan Beberapa Varietas Padi - Ajat Zatmika; Tineke Mandang; Wawan Hermawan; I Dewa Made Subrata; Agus Sutejo (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Quantity and quality of rice grain can be developed through more efficient and accurate threshing methods based on the measurement of threshing force (TF). This study aimed to investigate the influence of rice varieties and grain position on the panicle on the threshing force (TF) results. Rice grains from several harvested varieties were dried to a moisture content level of 12% and prepared for threshing force (TF) testing. The research design used was a 2-factor completely randomized design with 3 replications. The first factor was rice varieties consisting of 4 levels: Sintanur, Siliwangi, Pajajaran, and Cakrabuana. The second factor was grain position on the panicle, consisting of 3 levels: upper, middle, and basal. Threshing force (TF) values were tested for 12 treatment combinations. The obtained data were analyzed using analysis of variance (ANOVA) followed by Duncan's multiple range test (DMRT) at a significance level of 5%. The results indicated that rice varieties had a highly significant effect on the threshing force (TF). On the other hand, grain position on the panicle had a non-significant effect on the threshing force (TF). The rice variety that produced the highest average threshing force (TF) value was Cakrabuana with 0.51 N, followed by Siliwangi with 0.50 N, Sintanur with 0.43 N, and Pajajaran with 0.35 N. The upper position of the grains on the rice panicle yielded the lowest average threshing force (TF) value of 0.41 N, compared to the middle position with 0.46 N and the basal position with 0.47 N.